THE INFLUENCE OF INJECTION OF DEPOT MEDROXY PROGESTERONE ACETATE (DMPA) TO THE GLAND TISSUE HISTOLOGY BREAST ON WHITE RATS BREASTFEEDING - Asmita Dahlan (Jurnal Ipteks Terapan, 2018)
Depo MedroxyProgesteroneAcetate (DMPA) allegedly have the effect of breast glandular tissue breast-feeding women, and to prove it then conducted research into how the influence of injection of DMPA to the gland tissue histology breast.This research is experimental research design with post test only control group design that was implemented starting carried out in laboratories of pharmaceutical Faculty of Science and anatomic pathology laboratory andalas university medical school fields, the total sample 27 white female rats lactating drawn at random by age 2-3 months, weight 160-200 grams, divided into 3 groups consisting of the control group, treatment group 1 (DMPA 150 mg) and treatment group 2 (DMPA 300 mg). DMPA injections done in intra muscular  every 5 days during 4x injections (20 days). Research data were statistically processed using anova test with 95% confidence.Results showed that there are differences in the development of lobulus and asinus in the control group and treatment group.Conclusions of this study is the effect of DMPA injections in female rats breastfeeding on the area and the development of lobular breast lobes as well as breast acini Depo Medroxy Progesterone Acetate (DMPA) diduga mempunyai efek terhadap jaringan kelenjar payudara wanita menyusui, Untuk membuktikanya maka dilakukan penelitian bagaimana  pengaruh suntikan DMPA terhadap histologi jaringan kelenjar payudara. Penelitian ini adalah penelitian ekperimental dengan desain Post Test only control group design dilakukan di Laboratorium Farmasi Fakultas MIPA dan Laboratorium Patologi Anatomi Fakultas Kedokteran Universitas Andalas Padang. Sampel sebanyak 27 tikus betina putih yang menyusui, diambil secara acak, usia 2-3 bulan, berat 160 – 200 gram, dibagi menjadi 3 kelompok yang terdiri dari kelompok kontrol, kelompok perlakuan 1 ( DMPA 150 mg) dan kelompok perlakuan 2 (DMPA 300 mg). Penyuntikan DMPA dilakukan secara intramuskuler (IM) setiap 5 hari selama 4x penyuntikan  ( 20 hari ). Analisa data menggunakan uji Anova dengan kepercayaan 95 %. Hasil penelitian menunjukkan bahwa terdapat perbedaan perkembangan lobulus  dan asinus payudara pada kelompok kontrol dan kelompok perlakuan, maka disimpulkan adanya pengaruh suntikan DMPA pada tikus menyusui terhadap area lobular payudara dan perkembangan lobus serta asinus payudara. Disarankan perlu dipertimbangkan DMPA sebagai metode kontrasepsi pada ibu menyusui dan dapat dilakukan penelitian lebih lanjut tentang bagaimana pengaruh DMPA terhadap jaringan kelenjar  payudara dan Air Susu Ibu